Composition, Antimicrobial and Antioxidant Activities of the Essential Oil of Murraya exotica from Hainan of China - Huang, Ya-Si; Wang, Yong; Luo, Xi-Ping; Yuan, Ke (Asian Journal of Chemistry, 2013)
The objective of the works reported here was to make a thorough inquiry of composition, antimicrobial and antioxidant activities of the essential oil of Murraya exotica from Hainan Province, China. The essential oil of Murraya exotica were extracted by hydrodistillation and analyzed by GC and GC/MS. The relative content of each peak were detected by the normalization method of peak area. Thrity four components of Murraya exotica essential oil were identified which accounted for 97.76 % of total essential oil and the content of caryophyllene was up to 45.51 %, particularly. The results of the antioxidant activity test showed that the volatile oil had significant free radical scavenging capacity (IC50 = 0.1511). The antibacterial test results showed that the volatile oil of Murraya exotica had broad-spectrum antimicrobial activity on all bacteria other than Pseudomonas aeruginosa. Of which, the inhibition to Bacillus subtilis was about four times of the positive control and had a certain antifungal capabilities. Volatile oil of Murraya exotica had a certain antioxidant and antibacterial activity. The results can provide reference for further research on the chemical components of Murraya exotica volatile oil as well as for the exploration and utilization of it.